دور الاستقرار السياسي كعامل أساسي إلى جانب المتغيرات الاقتصادية الكلية في جذب الاستثمار الأجنبي المباشر في الجزائر: دراسة قياسية باستخدام نموذج الانحدار الذاتي ذي الفجوات الزمنية الموزعة المتباطئة ( ARDL ) خلال الفترة ( 1987- 2016 ) - بن مريم، محمد Ibn Mohammed, Mariam (جامعة حسيبة بن بوعلي بالشلف, 2018)
تناولت هذه الورقة محددات الاستثمار الأجنبي المباشر في الجزائر في ضوء التغيرات السياسية التي مرت بها الجزائر منذ 1987، بهدف التعرف على أهم عوامل جذب الاستثمار الأجنبي المباشر خلال هذه المرحلة، ولا سيما في ظل الجهود التي بذلتها الدولة في تحسين بيئة ممارسة العمل في الجزائر، وتقدم هذه الورقة تحليل لسبب تراجع نصيب الجزائر من الاستثمار الأجنبي المباشر مقارنة بدول أخرى في نفس المنطقة من خلال التركيز على دراسة أثر أهم المتغيرات الاقتصادية الكلية بالإضافة إلى التغيرات السياسية على الاستثمار الأجنبي المباشر في الجزائر. بينت هذه الدراسة أن أهم المتغيرات التي ساهمت في جذب الاستثمار الأجنبي المباشر خلال فترة الدراسة (والتي تربطه بها علاقة طردية) بالترتيب حسب حجم التأثير في الأجل الطويل هي: سعر الصرف، الصادرات، الواردات، وأخيرا النفقات العمومية، أما المتغيرات التي ساهمت في عزوفه بالترتيب حسب حجم التأثير هي: الوضع الأمني، أسعار البترول، سعر الفائدة، التضخم، حجم الديون، المعروض النقدي، وأخيرا حجم الضرائب. كما توصلت هذه الدراسة إلى أن عدم الاستقرار السياسي والاقتصادي وإعلان الحرب على الإرهاب في الجزائر خلال الفترة 1990-2001 مثلت أهم معوقات جذب الاستثمار الأجنبي المباشر خلال فترة الدراسة، لذا بينت الدراسة بأن سرعة تحقيق الاستقرار السياسي والأمني ووضع رؤية اقتصادية واضحة تستهدف تحقيق الاستقرار الاقتصادي والمستوى العام للأسعار، وأخيرا إنهاء الحرب على الإرهاب والمحافظة على نسب الأمن عند معدلاتها الطبيعية هي التي كانت تمثل العامل الكبير في استعادة استقطاب الاستثمار الأجنبي.
This article examines the determinants of foreign direct investment in Algeria in light of the political changes Algeria has experienced since 1987, in order to identify the most important factors for attracting foreign direct investment at this stage, especially in the light of the efforts of the State to improve the environment of the practice of work in Algeria. This article provides an analysis of why Algeria's share of foreign direct investment has declined relative to other countries in the same region, through the study of the impact of the most important macroeconomic variables in addition to political changes on foreign direct investment in Algeria. This study shows that the most important variables which contributed attract foreign direct investment during the study period (which have a positive relationship) according to the importance of long-term influence are: Exchange rate, exports, imports and finally public expenditure, As for the variables that contributed to reluctance the IDE in order according to the magnitude of the effect are: The security situation, oil prices, interest rates, inflation, external debt, the money supply, and finally taxes. The study also found that the political and economic instability and the declaration of the war against terrorism in Algeria during the period 1990-2001 represented the main obstacles to the attraction of foreign direct investment during the period 'study, So the study showed that the rapid political and security stability and the establishment of a clear economic vision were aimed at achieving economic stability and the general level of prices, and finally put an end to the war against terrorism and maintain the rates of safety in their natural rates, which has been the main factor restoring the attractiveness of foreign investment.
Keywords: الاستقرار السياسي; الاستثمار الأجنبي المباشر; نموذج ARDL; الجزائر; علاقة التكامل المشترك